Shifting, Not Changing: Adaptive Continuity in Indonesia’s Educational Policy Innovation Toward Quality Learning. - Sumarta; Sarwo Edy; Rosidin; Dinata Firmansyah (Penerbit Hellow Pustaka, 2025)
This study aims to unpack the paradigm of